Assessment of the coordination of low-carbon development and socio-economic development based on a comprehensive model: A case study of Anhui Province (China) - Qinfeng Xing; Ziwei Yang (Frontiers Media S.A., 2022)
The coordination of low-carbon development and socio-economic development has been the favorite subject of carbon emission reduction with the proposal of "dual carbon" goal. So an evaluation indicator system based on four dimensions of resource environmental endowment, energy environmental endowment, economic development endowment and social development endowment was constructed. And then, entropy weight method, coupling coordination level model, synergy degree model and gray forecasting method were used for comprehensive analysis based on the data from 2011 to 2020 in Anhui Province (China). The results show: 1) Low-carbon development lagged behind socio-economic development; 2) Low-carbon development and socio-economic were mutually beneficial; 3) The coordinated level of low-carbon development and socio-economic development in Anhui province was continuously improved, and the ordered structure will be realized in 2024 and 2029 respectively. This study deepens the theoretical cognition of carbon emission reduction, and the following countermeasures are formed: Highlighting the strategic guidance of sustainable development, perfecting the new regulatory mechanisms for carbon emission reduction, and innovating the science and technology to resolve major development crises.